2022
DOI: 10.1039/d1ra09371a
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenerated chemiluminescence of a Ru(bpy)32+/arginine system: a specific and sensitive detection of acetaminophen

Abstract: We use arginine as an alternative co-reactant for Ru(bpy)32+ by taking advantage of its low cost, non-toxicity, and biocompatibility. It is promising to expand the scope of the Ru(bpy)32+/Arg system and move forward their applications in bioassays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The ECL sensor can be applied for different phenols analysis, such as phenol, 23 and acetaminophen. 26 The relationship of different phenols and ECL intensity is below. 27,28 The efficiency of ECL quenching is directly related to the position and number of the substituent on the aromatic ring, 28 with meta derivatives displaying the greatest magnitude of quenching, and para derivatives the least.…”
Section: Cat Analysismentioning
confidence: 99%
“…The ECL sensor can be applied for different phenols analysis, such as phenol, 23 and acetaminophen. 26 The relationship of different phenols and ECL intensity is below. 27,28 The efficiency of ECL quenching is directly related to the position and number of the substituent on the aromatic ring, 28 with meta derivatives displaying the greatest magnitude of quenching, and para derivatives the least.…”
Section: Cat Analysismentioning
confidence: 99%
“…Furthermore, graphitic carbon nitride (g-CN) NMs as novel co-reactants also have the capacity to amplify the anodic ECL of Ru(bpy) 3 2+ since their surface has intrinsic amine-bearing groups [ 181 ]. In place of TPrA, arginine has also been established as an alternate co-reactant for Ru(bpy) 3 2+ owing to its low cost, biocompatibility, and non-toxicity [ 182 ]. Kitte et al [ 183 ] also reported on as a novel co-reactant thioacetamide (TAA) for Ru(bpy) 3 2+ through an anodic route and this system was used to determine TAA with a low LoD of 0.035 μM.…”
Section: Fundamentals Of Electrochemiluminescence: a Summarymentioning
confidence: 99%
“…Researchers, including Liu et al, have made advancements in this area by developing self-healing hydrogels for ECLbased sensing applications. [93][94][95][96][97][98][99] They prepared the transparent self-healing oxidized sodium alginate/hydrazide polyethy-lene glycol (OSA/PEG-DH) hydrogel by dynamically crosslinking covalent acylhydrazone bond. The IL 2-hydroxy-N,N,Ntrimethylethanaminium chloride and the luminescent reagent N-(aminobutyl)-N-(ethylisoluminol) (ABEI) were simultaneously immobilized in the OSA/PEG-DH hydrogel to obtain the ABEI/IL/OSA/PEG-DH hydrogel.…”
Section: Electrochemical Sensingmentioning
confidence: 99%